Análisis de los procesos de inventario con la utilización de la inteligencia artificial para la toma de decisiones financieras en la empresa automotriz ABC - Chacaguasay Guaman, Kevin Nehemias (2024)
This study investigates how artificial intelligence (AI) can optimize inventory processes at ABC automotive company to improve financial decision making. The company faces significant challenges due to reliance on traditional methods, which has led to overstocking and shortages, affecting its profitability and competitiveness. Through a comprehensive analysis, the potential benefits of AI are identified, such as anticipating demand through predictive analytics, automating processes, and optimizing inventory levels. The research demonstrates that AI can improve data accuracy and facilitate more efficient financial decisions. In addition, the challenges of its implementation are assessed, including the need for initial investment and staff training. The results indicate that the adoption of AI not only solves current inventory management problems, but also strengthens the company's long-term sustainability and competitiveness. This work provides a comprehensive view on how technology can transform operational management in the automotive industry, offering practical recommendations for implementing AI in inventory management and improving the company's financial performance.